2015
DOI: 10.1186/s12957-015-0682-7
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive surgery and perioperative intraperitoneal chemotherapy for peritoneal carcinomatosis in the elderly

Abstract: BackgroundPeritoneal carcinomatosis is life-threatening without cytoreductive surgery (CRS) and perioperative intraperitoneal chemotherapy (PIC). Only a few studies in the literature addressed the relationship between age and outcomes of peritonectomy. This study was designed to review the clinical outcomes in elderly patients who underwent CRS and PIC.MethodsThis is a retrospective study of prospectively collected data of 611 consecutive patients with peritoneal carcinomatosis who underwent CRS and PIC by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Our results demonstrated no statistically significant difference in OS despite increased mortality in the older population. While this has similarly been reported in the literature ( Table 5 ), there are also several other studies which have demonstrated worse OS outcomes for older patients [ 29 ], [ 30 ], [ 31 ], [ 32 ], [ 33 ], [ 34 ], [ 35 ], [ 36 ], [ 37 ], [ 38 ]. However, many of these studies consisted of small sample sizes and were undertaken in small peritonectomy units, thus, results may be confounded by inexperience or low case volumes for operating on older patients.…”
Section: Discussionsupporting
confidence: 78%
“…Our results demonstrated no statistically significant difference in OS despite increased mortality in the older population. While this has similarly been reported in the literature ( Table 5 ), there are also several other studies which have demonstrated worse OS outcomes for older patients [ 29 ], [ 30 ], [ 31 ], [ 32 ], [ 33 ], [ 34 ], [ 35 ], [ 36 ], [ 37 ], [ 38 ]. However, many of these studies consisted of small sample sizes and were undertaken in small peritonectomy units, thus, results may be confounded by inexperience or low case volumes for operating on older patients.…”
Section: Discussionsupporting
confidence: 78%
“…The postoperative mortality was 2 % and 3 % in the 2 groups respectively and there was no difference in the overall survival as well. [40] Three other retrospective studies with smaller number of patients have concluded the same. [41][42][43] The above evidence strongly suggests that age alone can not be a contraindication for the procedure.…”
Section: Agementioning
confidence: 75%
“…In patients with peritoneal cancer index less than six, 5‐year survival approached 50% in a large retrospective series . Further, an Australian study of 611 patients demonstrated that cytoreductive surgery can be successfully performed in the elderly with equally good results . Of note, femoral nerve injuries are not uncommonly reported after pelvic surgery in around 2% of cases .…”
mentioning
confidence: 99%